Penerapan Permainan Engklek dalam Menstimulasi Kemampuan Motorik Kasar Anak Kelas B TK Mekar Mentari Gemilang - Umi Salsabela; Yuniarti Yuniarti; Iin Maulina (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
The importance of traditional games in providing character education and positive moral values for children's growth, especially in developing gross motor skills. Initial observations showed that children's gross motor skills were still low due to a lack of interest in traditional games and teachers had not found the right method. This study aims to describe the description of children's gross motor skills before and after being given the game engklek. Using a quantitative approach with a pre-experimental method and pretest-posttest design, the research was conducted on 9 children aged 5-6 years at Mekar Mentari Gemilang Kindergarten. Data was collected through observation, interviews, and checklists. The results showed a significant increase in children's gross motor skills after being given the cranklek game Treatment, with an average pre-test score of 4.33 increasing to 8.00 in the post-test. The findings imply that traditional cricket games are effective in stimulating children's gross motor development.